Integrative Analysis Reveals Genes Causal Relation with Ovarian Cancer and aging - Qin, Lan-hui; Yang, Chongze; Song, Rui; Chen, Pei-yin; Jiang, Zijian; Xu, Weihui; Zeng, Guanzhen; Liao, Jin-yuan; Long, Liling (Current Topics in Medicinal Chemistry, 2025)
<span class=
Keywords: single-cell RNA sequencing